Symbolic Representations Of Emotions In ‘Sonnet From The Portuguese’ - Naomi, Larita; Indriani, Ketut Santi; Netra, I Made (Peneliti.net, 2025)
This research aims to find out symbolic representation of emotion found in ‘Sonnet from the Portuguese’ by Elizabeth Barrett Browning, using Roland Barthes’ semiotic theory of denotation and connotation. Focusing on five selected sonnets (1, 6, 14, 22, and 43), the research highlights important symbolic elements, such as metaphor and imagery of love, longing, doubt, passion, and suffering, demonstrating the poet’s emotional depth. Although Browning’s thematic and biographical elements have been examined in earlier research, this analysis closes a significant gap by methodically interpreting the semiotic structures that support the Sonnet’s emotional expression. The study provides fresh insights into the relationship between language and emotion in Victorian love poetry by utilizing Barthes’ framework to show how superficial imagery (denotation) is transformed into more profound emotional meaning (connotation). This study is important because it increases our knowledge of Browning’s literary technique and shows how semiotic theory may clarify the complex emotional representation found in poetry.